2014
DOI: 10.3109/08977194.2014.984805
|View full text |Cite
|
Sign up to set email alerts
|

BMP-4 increasesactivin Agene expression during osteogenic differentiation of mouse embryonic stem cells

Abstract: Activin A is a growth factor released by mature osteoblasts that has a critical effect on bone formation. We investigated the effect of bone morphogenetic protein (BMP)-4 on activin A gene expression during in vitro osteogenic differentiation of mouse embryonic stem (ES) cells. Embryoid bodies were cultured in retinoic acid (RA) for three days and then without RA for two days. Seeded cells received osteogenic medium with β-glycerophosphate, L-ascorbic acid 2-phosphate and dexamethasone during 19 days, with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Previous studies demonstrated that application of activin A in the parietal bone led to upregulation of bone formation in newborn rats [39] and mice [40]. An in vitro study demonstrated that activin A contributed to osteogenesis of mouse embryonic stem cells [41] and promoted osteoblastic differentiation of murine bone marrow cells [38] and murine myoblasts [42]. Consistent with these reports, our results demonstrated that activin A was expressed in Saos2 cells and promoted osteoblastic differentiation of Saos2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies demonstrated that application of activin A in the parietal bone led to upregulation of bone formation in newborn rats [39] and mice [40]. An in vitro study demonstrated that activin A contributed to osteogenesis of mouse embryonic stem cells [41] and promoted osteoblastic differentiation of murine bone marrow cells [38] and murine myoblasts [42]. Consistent with these reports, our results demonstrated that activin A was expressed in Saos2 cells and promoted osteoblastic differentiation of Saos2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…The reason for this temporal-and spatial-dependent pattern of expression is still unclear; however, these are intense periods of hypertrophic chondrogenesis and bone mineralization. Activin A is involved in the early embryonic processes of mesodermal formation (7,8,18) and in the differentiation of mesenchymal progenitor cells into chondrogenic and osteogenic fates (50,106). In addition, activin A signaling controls digit skeletogenesis (281), early development of jaw, teeth, and palate (120,271), and embryonic left/right patterning (309).…”
Section: Activin a In The Musculoskeletal Systemmentioning
confidence: 99%
“…Several recent studies have focused on differentiating both ESCs and iPSCs into osteoblasts [8][9][10]. ESCs and iPSCs can be differentiated to the osteoblast lineage by first forming embryoid bodies (EBs), in which mesoderm lineage cells differentiate to osteoblast lineage cells under osteogenic factors including ascorbic acid, ßglycerophosphate, and dexamethasone [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. ESCs and iPSCs can also be differentiated to osteoblast lineage cells through monolayer culture without first forming suspended EBs [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%